The role of procedural fairness in the relationship between budget participation and motivation - Zainuddin, Suria; Isa, Che Ruhana (American-Eurasian Network for Scientific Information, Jordan, 2011)
Previous studies have provided inconsistent empirical findings in the relationship between budget participation and motivation. It is argued that these conflicting findings may be due to mediating variables. Fairness consideration may be an essential mediating variable that may increase the motivation of employees. Thus, the purpose of this study is to examine the mediating role of procedural fairness in the relationship between budget participation and motivation. The fairness perceptions of employees are important because they can demotivate the employees if any unfair conditions exist in budget creation. The fairness perceptions also ensure that all members of the organization are motivated to achieve the organization's goals. The framework of this study is developed based on the goal setting theory. Through the involvement of managers in preparing budget, a clearer and attainable budget can be set, which fosters the motivation level of individuals. Goal setting theory also recognized the importance of reasonable and fair goals as it enhances favorable attitude and behavior of employees in the organization. However the effect of fairness perceptions in the relationship between budget participation and motivation has not been systematically evaluated. As such, using the goal setting theory, this study attempts to examine whether budget participation increases the perceptions of fairness, which in turn increases motivation. It is argued that by participating in the budget setting process, a fair budget can be determined from a fair process employed, thus increasing the likelihood of improving individuals' motivation. Utilizing the Partial Least Square technique in analyzing data, based on survey questionnaires of Malaysian managers, the results are as expected. Procedural fairness plays a role as mediating variable in the relationship between budget participation and motivation. This result suggests the importance of maintaining fairness in the management control system in the organization. The involvement of managers in budget setting process promotes a favorable behavior of the managers that increase their perception of fairness which may consequently increase their motivation.